Validation of the Japanese Version of the Burnout Assessment Tool - Sakakibara, Keiko; Shimazu, Akihito; Toyama, Hiroyuki; Schaufeli, Wilmar B. (Frontiers in Psychology, 2020)
The current study aimed to validate the Japanese version of the Burnout Assessment Tool (BAT-J), a new burnout measure. We conducted an Internet survey to confirm the validity and reliability of BAT-J, using registered monitors from a Japanese survey company. The first-wave survey was conducted in May 2018, with 1,032 monitors. Of these, 498 participated in the second-wave survey in June 2018 to confirm one-month test-retest reliability. We examined the factorial validity of the BAT-JC and BAT-JS, representing the core and secondary burnout symptoms, respectively, as well as their reliability (internal consistency and test-retest reliability), and construct validity. Convergent and discriminant validity were examined using a multitrait-multimethod framework as well as the average variance explained. Results of the confirmatory factor analysis showed that the four-factor model for the BAT-JC and two-factor model for the BAT-JS had the best fit to the data. Reliability was confirmed in terms of internal consistency and test-retest reliability. We confirmed convergent and discriminant validity of the BAT-JC vis-ȧ-vis burnout, as assessed with the Maslach Burnout Inventory – General Survey. Moreover, external discriminant validity of the BAT-J was demonstrated for work engagement and workaholism. Finally, both BAT scales showed significant positive relationships with job demands, psychological distress and turnover intention. All validity results were in line with the job demands-resources model. The results of the current study provide the first evidence for the reliability and the factorial and construct validity of the BAT-J.